The economics of badmouthing: Libel law and the underworld of the financial press in France before World War I - Vincent Bignon; Marc Flandreau (Graduate Institute of International and Development Studies, 2010)
This article analyzes the economics of badmouthing in the context of the pre-1914 French capital market. We argue that badmouthing was a means through which racketeering journals sought to secure property rights over issuers' reputation. We provide a theoretical study of the market setup that emerged to deal with such problems, and we test our predictions using new evidence from contemporary sources.
Keywords: 330; Wirtschaftszeitschrift; Öffentliche Meinung; Finanzmarktregulierung; Geschichte; Frankreich